2010
DOI: 10.1167/iovs.09-3720
|View full text |Cite
|
Sign up to set email alerts
|

Heritabilities of Ocular Biometrical Traits in Two Croatian Isolates with Extended Pedigrees

Abstract: While heritabilities of CT and CC seemed uniformly high across studies of Caucasian datasets, estimates for SER varied widely and were at the lower end of the spectrum of published observations in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…By comparing growth trajectories in children with the stature of their parents, Botton et al 40 have shown that this relatively straightforward scenario hides a complex interplay of maternal and paternal genetic, epigenetic or shared environment effects, alternating in their impact at different stages of childhood. Our findings regarding the growth trajectories of height (and weight) and ocular component dimensions at age 15, were in accordance with the consensus from previous work [13][14][15][16][17][18][19]25 , namely, that tall individuals tend to have larger eyes (a longer axial length and a flatter cornea). Again, however, the magnitude of these associations in the ALSPAC cohort was modest -explaining at most a few percent of the natural variation in AXL and RCC at age 15 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By comparing growth trajectories in children with the stature of their parents, Botton et al 40 have shown that this relatively straightforward scenario hides a complex interplay of maternal and paternal genetic, epigenetic or shared environment effects, alternating in their impact at different stages of childhood. Our findings regarding the growth trajectories of height (and weight) and ocular component dimensions at age 15, were in accordance with the consensus from previous work [13][14][15][16][17][18][19]25 , namely, that tall individuals tend to have larger eyes (a longer axial length and a flatter cornea). Again, however, the magnitude of these associations in the ALSPAC cohort was modest -explaining at most a few percent of the natural variation in AXL and RCC at age 15 years.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, studies in newborns, children and adults have demonstrated associations between body stature and axial eye length, providing indirect evidence for co-ordinated growth of the eye and body (after adjusting for the typically observed difference in axial length between the sexes) [11][12][13][14][15][16][17][18][19][20][21] . Direct support for a causal association comes from studies of individuals who fail to produce insulin-like growth factor 1 (IGF-1) due to growth hormone (GH) deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al, 2010), isolate population studies (e.g. Choh et al, 2001; Williams‐Blangero et al, 2002; Wijsman et al, 2003; Vitart et al, 2010;), in addition to studies from the Utah Population Database (e.g. Camp et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Heritability of ocular traits, the variation in a phenotypic trait that is attributable to genetic factors, can be high. For example, estimates for the heritability of IOP is 0.29–0.50, VCDR is 0.48–0.80, CCT is 0.71–0.95 and RNFL thickness is 0.48 (Chang et al, 2005; Charlesworth et al, 2010; Klein et al, 2004; Levene et al, 1970; Schwartz et al, 1975; Toh et al, 2005; van Koolwijk et al, 2007; Vitart et al, 2010a; Zheng et al, 2008). These traits, used to study and dissect a variety of ocular disorders, are individually addressed below.…”
Section: Genetic Analyses Of Poag-associated Traits (Endophenotypes)mentioning
confidence: 99%